XSTRIP—a silicon microstrip-based X-ray detector for ultra-fast X-ray spectroscopy studies - Headspith, Jon; Salvini, G; Thomas, S.L; Derbyshire, G; Dent, A; Rayment, T; Evans, J; Farrow, R; Anderson, C; Cliche, J; Dobson, B.R (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2003)
For a number of years, an exciting and important area of synchrotron radiation science has been X-ray absorption spectroscopy fine structure studies of dynamically changing samples on the sub-second time-scales. By utilizing this technique, precise measurement of detailed structural changes can be investigated during a chemical or phase change reaction without the need for repeated experiments or expensive stopped flow techniques. Until recently, instrumentation to facilitate these studies has been based on commercially available detectors developed predominantly for other applications. Whilst these systems have yielded quality science, they have been subject to a number of fundamental limitations, particularly their speed, linearity and dynamic range. We have developed a new detector, XSTRIP, to overcome some of these. This new instrument marries dedicated silicon microstrip technology with specialist low noise, custom developed, fast readout integrated circuits, to yield an instrument that will unlock whole new areas of science to researchers. This paper will discuss some of the drawbacks of historical systems, give details of the XSTRIP system and also present the operating parameters of the system. In addition, some of the initial scientific experimental results will also be presented.